Regularity abrasive particle, abrasive wheel slurry and preparation method of thinned abrasive wheel
By preparing regular abrasive grains and grinding wheel slurry, the efficiency and damage problems in machining brittle and hard materials were solved, achieving high-efficiency cutting at high speeds and precise thinning of workpieces.
Patent Information
- Application Number
- CN202411625170.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2025-01-07
AI Technical Summary
Existing technologies suffer from low production efficiency, low yield, and easy breakage and scratching of workpieces when processing brittle and hard materials. In particular, grinding wheels using metal-bonded rollers are difficult to maintain cutting ability and service life under high-speed conditions.
The grinding wheel slurry with regular abrasive grains is prepared by mixing, shaping, sintering and post-treatment. The abrasive grains are angular and have pores on the surface. High-temperature resistant powder is combined to maintain the shape and cutting force. The grinding wheel slurry with resin and filler is light and heat cured to form a thinned grinding wheel.
Maintaining high cutting efficiency at high speeds reduces workpiece chipping, cracking, and scratches, thus improving grinding wheel life and workpiece machining accuracy.
Smart Images

Figure CN119260625A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of grinding materials, in particular to abrasive grains in a grinding wheel, and more particularly to a preparation method of regular abrasive grains, grinding wheel slurry and a thinned grinding wheel. Background Art
[0002] With the rise of the Internet of Things and the popularization of virtual display technology, people have higher and higher requirements for visualization instruments. Human-computer interaction interfaces mostly use brittle and hard transparent materials, such as glass, sapphire, quartz, etc. However, such brittle and hard materials are easily broken due to fine cracks, so their processing has always faced defects such as low production efficiency and low product yield.
[0003] Traditionally, single-sided or double-sided grinding machines are used to process such brittle and hard materials. The processing equipment has a low rotation speed, generally less than 100r / min. In addition, since the pressurization method is cylinder pressurization, the thickness of the finished workpiece is more dependent on manual labor and experience. The thickness of the workpiece is controlled by the length of processing time, which makes it difficult to achieve efficient automation and cannot meet the growing demand for brittle and hard materials in the market.
[0004] At present, the industry has considered the rapid thinning methods and processes for brittle and hard materials from the aspect of processing equipment, such as the use of new grinding machines. The grinding disc in the equipment has a high rotation speed, generally above 200r / min, and up to 2000r / min. In addition, in order to improve the accuracy of the thickness of the workpiece output, this type of equipment does not use the cylinder pressurization method, but generally uses the method of grinding disc tilting or screw rod progressive, and accurately controls the thickness of the workpiece output through the displacement of the screw rod or the angle of the grinding disc. Generally, the discharge position is the minimum spacing when the upper and lower grinding discs are tilted.
[0005] Currently, high-speed equipment on the market can improve production efficiency, but the grinding wheels or grinding wheels used in conjunction with them mostly use metal binders and need to be sintered at high temperatures. The hardness of the finished product is relatively high. When used with high-speed equipment with an inclined angle to process brittle and hard materials, such as glass, sapphire, quartz, silicon carbide, etc., there are generally edge cracking, irregular scratches, and many dressing times. At present, the industry has also made improvements to grinding wheels or grinding wheels to solve problems such as workpiece surface damage. For example, the abrasive grains in the grinding wheel are regular spherical. Although it can greatly reduce scratches, the grinding wheel has insufficient grip on the spherical abrasive grains, resulting in insufficient cutting ability of the grinding wheel at high speeds and a short service life. Summary of the invention
[0006] Based on the above problems, the purpose of the present invention is to provide a method for preparing abrasive grains with regularity, grinding wheel slurry and thinning grinding wheel. The abrasive grains used for thinning grinding wheel have higher cutting force, can maintain high cutting efficiency at high rotation speed of the grinding disc, can also reduce the edge collapse, cracks, scratches and the like of the workpiece, and the degree of damage to the workpiece can be controlled.
[0007] To achieve the above-mentioned purpose, the present invention provides, on the one hand, a regular abrasive grain, which is in the form of regular angular particles and has pores on the surface, with a side length of 50 to 2000 μm, a porosity of 10 to 50%, and a pore diameter of 5 to 50 μm. In terms of weight percentage, the preparation raw materials include 20 to 90 parts of abrasive base, 20 to 50 parts of quartz powder, 1 to 20 parts of adhesive, 1 to 10 parts of solvent, 1 to 50 parts of high temperature resistant powder and 0 to 10 parts of other additives, and the melting point of the high temperature resistant powder is higher than the sintering temperature of the preparation raw materials during sintering.
[0008] In the technical solution adopted by the present invention, the raw material contains high temperature resistant powder with a melting point higher than the sintering temperature, which acts as a placeholder in the process of preparing abrasive grains using abrasive grain base material, quartz powder and adhesive, etc., and can prevent the adhesion of abrasive grains, thereby maintaining the shape of the grains. The abrasive grains are regular granules with edges and corners and have pores on the surface, with a side length of 50 to 2000 μm, a porosity of 10 to 50%, and a pore diameter of 5 to 50 μm. The abrasive grains have strong cutting force and can generate strong force with the matrix material in the thinning grinding wheel, that is, the matrix material in the thinning grinding wheel has a strong holding force on the abrasive grains, so that high cutting efficiency can be maintained at a high rotation speed of the grinding disc, so that the workpiece can be quickly thinned to the target value within the set processing time, reducing the damage of the grinding disc angle to the workpiece, such as extrusion, edge collapse, and cracking.
[0009] As a technical solution of the present invention, the abrasive base includes a main abrasive base and a secondary abrasive base, the hardness and size of the main abrasive base are both greater than those of the secondary abrasive base, and the main abrasive base and the secondary abrasive base are each independently selected from at least one of diamond, silicon carbide, boron carbide, aluminum oxide, cerium oxide, titanium diboride, tungsten carbide, titanium carbide, cubic boron nitride, garnet, zirconium oxide and titanium oxide.
[0010] As a technical solution of the present invention, the Mohs hardness of the primary abrasive base is at least 8 or the Dv50 of the secondary abrasive base is 0.5-9.0 μm.
[0011] As a technical solution of the present invention, the quartz powder is a single quartz powder.
[0012] As a technical solution of the present invention, the quartz powder is a mixture of multiple quartz powders with a melting point not higher than 1000°C.
[0013] As a technical solution of the present invention, the particle size of the quartz powder is smaller than the particle size of the abrasive base.
[0014] As a technical solution of the present invention, the adhesive includes at least one of silicate, phosphate, aluminate, colloidal sodium hydroxide, a saturated aqueous solution of PVA and dextrin.
[0015] As a technical solution of the present invention, the volatilization point of the adhesive is 200-500°C.
[0016] As a technical solution of the present invention, the solvent includes pure water, and the electrical conductivity is less than 10 μs / cm.
[0017] As a technical solution of the present invention, the high temperature resistant powder includes at least one of sodium chloride, sintered alumina, CoCl2, MnCl2, FeCl2 and CaCl2.
[0018] As a technical solution of the present invention, the other auxiliary agents include at least one of a wetting agent, a defoaming agent and a bactericide.
[0019] As a technical solution of the present invention, the abrasive particles are triangular pyramids, quadrangular pyramids, triangular prisms or quadrangular prisms.
[0020] A second aspect of the present invention provides a method for preparing regular abrasive particles, comprising the steps of:
[0021] (I) Mixing
[0022] Mixing the formulated amount of abrasive base, quartz powder, binder, solvent and other additives to obtain a thick mixture;
[0023] (ii) Finalization
[0024] The thick mixture is pressed into the cavity of a mold having certain edges and corners, and dried to obtain shaped abrasive particles;
[0025] (III) Sintering
[0026] The abrasive grains and high temperature resistant powder are mixed and then sintered, and the melting point of the high temperature resistant powder is higher than the sintering temperature;
[0027] (IV) Post-processing
[0028] After the sintered product is cooled, it is screened to remove the high temperature resistant powder and obtain regular abrasive grains.
[0029] In the preparation method of the present invention, raw materials such as abrasive base material, quartz powder, and adhesive are dried and shaped in a cavity of a mold with certain edges and corners to obtain abrasive particles with regular shapes and edges, and sintered together with high-temperature resistant powder having a melting point higher than the sintering temperature. The addition of high-temperature resistant powder can keep the abrasive particles from sticking together during sintering, reduce the deformation of the abrasive particles during sintering, and still maintain good regularity of the abrasive particles. After post-processing to remove the high-temperature resistant powder, regular abrasive particles can be obtained, so that the prepared grinding disc can still maintain high cutting efficiency at high speed. In addition, under the action of the high-temperature resistant powder, the abrasive particles can be sintered only at low temperature, so energy consumption is saved.
[0030] As a technical solution of the present invention, the mixing in step (I) can be carried out in a ball mill mixer, and the mixing time is 1 to 2 hours.
[0031] As a technical solution of the present invention, the depth of the cavity is 80 to 2000 μm, and the side length of the cavity wall is 80 to 2000 μm.
[0032] As a technical solution of the present invention, the drying temperature is 70-130° C., and the drying is performed until the water evaporates to more than 90 wt.%.
[0033] As a technical solution of the present invention, the abrasive particles are separated from the cavity by gravity, shaking, air gun blowing, ultrasonic vibration, and vacuum adsorption.
[0034] As a technical solution of the present invention, the high temperature resistant powder includes at least one of sodium chloride, sintered alumina, CoCl2, MnCl2, FeCl2 and CaCl2.
[0035] As a technical solution of the present invention, the maximum sintering temperature is 70-90% of the melting point of the high temperature resistant powder.
[0036] As a technical solution of the present invention, the maximum sintering temperature is 500-1000°C.
[0037] As a technical solution of the present invention, the sintering is carried out in steps, firstly heating the temperature to 300-450°C, and then heating the temperature to 500-1000°C.
[0038] As a technical solution of the present invention, the heating rate of the sintering is 1 to 10° C. / min.
[0039] As a technical solution of the present invention, the screening is performed using a water flow particle size classifier.
[0040] The third aspect of the present invention provides a grinding wheel slurry, wherein the raw materials for preparation include, by weight percentage, 7 to 60 parts of abrasive grains, 30 to 60 parts of resin, 5 to 30 parts of diluent, 0.5 to 5.0 parts of photoinitiator, 0.6 to 4.0 parts of thermal initiator, 40 to 60 parts of filler and 0 to 5 parts of auxiliary agent, and the abrasive grains are the aforementioned regular abrasive grains or the regular abrasive grains prepared by the aforementioned method for preparing regular abrasive grains.
[0041] The grinding wheel slurry of the present invention is a compound of resin and the above-mentioned regular granular abrasive grains with edges and corners and pores on the surface. The resin has a long molecular chain. After light and heat curing, the molecular chain can creep slightly and has a certain elasticity. Therefore, when the grinding wheel processes the workpiece, even if the abrasive grains have edges and corners, the workpiece will not be cracked, and the scratch depth can be controlled.
[0042] As a technical solution of the present invention, the resin includes at least one of epoxy resin, acrylic resin and polyurethane.
[0043] As a technical solution of the present invention, the surface hardness of the resin after curing is 60-95HA.
[0044] As a technical solution of the present invention, the diluent includes at least one of an acrylate compound, a vinyl compound, a vinyl ether compound and an epoxy compound.
[0045] As a technical solution of the present invention, the diluent includes at least one of n-butyl acrylate, isooctyl acrylate, isodecyl acrylate, lauryl acrylate, hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, styrene, vinyl acetate, n-vinyl pyrrolidone, ethylene glycol diacrylate, propylene glycol diacrylate and phenyl glycidyl ether).
[0046] As a technical solution of the present invention, the photoinitiator includes at least one of benzoin, benzoin ethyl ether, benzoin butyl ether, benzoin dimethyl ether, 2-hydroxy-2-methyl-1-phenyl ketone, 1-hydroxy-cyclohexyl-phenyl ketone, dibenzophenone, amine compounds, thioxanthenes, camphorquinone, bisimidazole, onium salts, metal organics and organosilane compounds.
[0047] As a technical solution of the present invention, the thermal initiator is an azo compound or a peroxide compound.
[0048] As a technical solution of the present invention, the thermal initiator includes at least one of azobisisobutyronitrile, azobisisoheptylnitrile, benzoyl peroxide, tert-butyl peroxide 2-ethylhexyl acid ester, tert-amyl peroxide 2-ethylhexyl acid ester, 1,1'-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane, tert-amyl peroxyacetate, tert-amyl peroxybenzoate, tert-butyl peroxytrimethylhexanoate, diisopropyl peroxide and di-tert-amyl peroxide.
[0049] As a technical solution of the present invention, the filler includes at least one of kaolin, alumina, nano-silicon dioxide, wollastonite, polyamide wax and talc.
[0050] As a technical solution of the present invention, the auxiliary agent includes at least one of a wetting agent, a coupling agent and a defoaming agent.
[0051] A fourth aspect of the present invention provides a method for preparing a grinding wheel slurry, comprising the steps of:
[0052] 1. Dry mixing
[0053] Mixing the abrasive grains, the filler and the additive to obtain a powder mixture;
[0054] ㈡Resin prepolymer preparation
[0055] The resin and the diluent are heated and stirred to obtain a resin prepolymer with a viscosity of less than 3000 mPa.s;
[0056] (iii) Preparation of slurry
[0057] The resin prepolymer, the photoinitiator and the thermal initiator are stirred and then added into the powder mixture to obtain a premix, and the premix is ball-milled to obtain a grinding wheel slurry.
[0058] In the preparation method of the grinding wheel slurry of the present invention, abrasive particles, fillers and additives are first mixed to obtain a powder mixture, and then diluted with a diluent to make the components evenly distributed. A resin prepolymer with stable and viscous components can be obtained by heating and stirring. A photoinitiator and a thermal initiator are compounded to obtain a grinding wheel slurry. Subsequently, a thinned grinding wheel can be obtained by photocuring and thermal curing, and the operation is convenient.
[0059] The fifth aspect of the present invention provides a method for preparing a thinned grinding wheel, comprising the steps of: coating the aforementioned grinding wheel slurry or the grinding wheel slurry prepared by the aforementioned grinding wheel slurry preparation method in a mold and then transferring it to a substrate and then sequentially performing ultraviolet light curing and thermal curing to obtain a combined layer; adhering the combined layer to one side of a support plate; and adhering a grinding disc to the other side of the support plate.
[0060] In the preparation method of the thinned grinding wheel of the present invention, the grinding wheel slurry is coated in a mold and then transferred to a substrate and then cured, so that not only the regular shape of the abrasive particles but also the regular shape of the grinding wheel slurry after curing can be maintained. In addition, light curing is first performed to fix the shape, so that the surface hardness can be achieved, and the appearance is easy to shape. Then, heat curing is performed to achieve high hardness inside the combined layer and improve the resin strength. The combined layer and the support plate have a certain elasticity and can withstand the impact during high-speed rotation. BRIEF DESCRIPTION OF THE DRAWINGS
[0061] Figure 1 It is a schematic diagram of the thinned grinding wheel of the present invention before being combined with the grinding disc.
[0062] Figure 2 This is an electron microscope image of the abrasive particles of Example 1.
[0063] Figure 3 This is an electron microscope image of the abrasive particles of Example 2. DETAILED DESCRIPTION
[0064] The thinning grinding wheel of the present invention comprises a support plate and a combination layer and a grinding disc located on both sides of the support plate. The support plate can be attached to the combination layer and the grinding disc by a pressure-sensitive adhesive or glue. The support plate can be made of plastic, such as a polyethylene plate, a polypropylene plate, a polycarbonate plate, a foamed polyurethane plate, etc. The support plate can also be made of a metal sheet, or a textile, etc. A release film can be attached to the support plate before being compounded to the grinding disc, such as Figure 1 As shown, before being compounded to the grinding disc, the support plate 10 can be a polycarbonate plate (PC plate), and a release film 50 is adhered to one side of the support plate 10 using a PSA pressure-sensitive adhesive 31, and a composite layer 70 is adhered to the other side using a PSA pressure-sensitive adhesive 33. The composite layer 70 includes a substrate 71 and a grinding wheel slurry solidified layer 73 compounded on the substrate 71. The thickness of the composite layer 70 is 0.2 to 1.9 mm. The substrate 71 can be a PET film, glass cloth, non-woven fabric, paper-based phenolic cloth, TPU, etc., preferably a PET film, and more preferably a PET film with a surface coating layer.
[0065] When preparing a thinned grinding wheel, the grinding wheel slurry can be coated in a mold and then transferred to a substrate and then UV-cured and thermally cured in sequence to obtain a combined layer; the combined layer is adhered to one side of a support plate; and a grinding disc is adhered to the other side of the support plate. After vacuum degassing the grinding wheel slurry, it is evenly coated on the abrasive tool by scraping and then transferred to the substrate. The cavity of the abrasive tool can be a prism or a pyramid. The shape of the formed grinding wheel slurry cured layer depends on the designed mold, but no matter what shape it is, it still needs to match the grinding disc. UV curing can be curing the substrate coated with the grinding wheel slurry under ultraviolet light waves of 320 to 400 nm for 2 to 30 seconds. Then thermal curing is performed, and thermal curing can be baking at 70 to 120°C for 1 to 48 hours.
[0066] In terms of weight percentage, the raw materials for preparing the grinding wheel slurry of the present invention include 7 to 60 parts of abrasive grains, 30 to 60 parts of resin, 5 to 30 parts of diluent, 0.5 to 5.0 parts of photoinitiator, 0.6 to 4.0 parts of thermal initiator, 40 to 60 parts of filler and 0 to 5 parts of auxiliary agent. Further, the abrasive grains may be, but are not limited to, 7 parts, 10 parts, 15 parts, 20 parts, 25 parts, 30 parts, 35 parts, 40 parts, 45 parts, 50 parts, 55 parts and 60 parts. The resin may be, but is not limited to, 30 parts, 35 parts, 40 parts, 45 parts, 50 parts, 55 parts and 60 parts. The resin includes at least one of epoxy resin, acrylic resin and polyurethane, which can be cured by thermal curing and light curing. The surface hardness of the resin after curing is 60 to 95HA, preferably 85 to 93HA. The diluent may be, but is not limited to, 5 parts, 7 parts, 10 parts, 15 parts, 20 parts, 25 parts, and 30 parts. The diluent includes at least one of acrylate compounds, vinyl compounds, vinyl ether compounds, and epoxy compounds. Further, the diluent includes at least one of n-butyl acrylate, isooctyl acrylate, isodecyl acrylate, lauryl acrylate, (meth) hydroxyethyl acrylate, (meth) hydroxypropyl acrylate, styrene, vinyl acetate, n-vinyl pyrrolidone, ethylene glycol diacrylate, propylene glycol diacrylate, and phenyl glycidyl ether. The photoinitiator may be, but is not limited to, 0.5 parts, 1.0 parts, 1.5 parts, 2.0 parts, 2.5 parts, 3.0 parts, 3.5 parts, 4.0 parts, 4.5 parts, and 5.0 parts. The photoinitiator includes at least one of benzoin, benzoin ethyl ether, benzoin butyl ether, benzoin dimethyl ether, 2-hydroxy-2-methyl-1-phenyl ketone, 1-hydroxy-cyclohexyl-phenyl ketone, benzophenone, amine compounds, thioxanthone, camphorquinone, bisimidazole, onium salt, metal organic matter and organosilane compounds. The thermal initiator can be, but is not limited to, 0.6 parts, 1.0 parts, 1.5 parts, 2.0 parts, 2.5 parts, 3.0 parts, 3.5 parts, and 4.0 parts. The thermal initiator is an azo compound or a peroxide compound. Further, the thermal initiator includes at least one of azobisisobutyronitrile, azobisisoheptanenitrile, benzoyl peroxide, tert-butyl peroxide 2-ethylhexyl acid, tert-amyl peroxide 2-ethylhexyl acid, 1,1'-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane, tert-amyl peroxyacetate, tert-amyl peroxybenzoate, tert-butyl peroxytrimethylhexanoate, diisopropylbenzene peroxide and di-tert-amyl peroxide. The filler can be, but is not limited to, 40 parts, 43 parts, 45 parts, 48 parts, 50 parts, 53 parts, 55 parts, 58 parts, and 60 parts. The filler includes at least one of kaolin, alumina, nano-silica, wollastonite, polyamide wax and talc, and the filler can be used to increase the static viscosity of the system, ensure the uniformity of the coating thickness, and increase the strength of the resin after curing. The auxiliary agent can be, but is not limited to, 0 parts, 1 parts, 2 parts, 3 parts, 4 parts, and 5 parts.The additives include at least one of a wetting agent, a coupling agent and a defoaming agent, wherein the wetting agent can improve the compatibility between the abrasive and the resin, and is preferably a polyammonium salt wetting agent; the coupling agent can increase the bonding strength between the abrasive and the resin to improve the wear resistance, and is preferably an aminosilane coupling agent and an epoxysilane coupling agent; the defoaming agent is preferably a polyether silicone oil to eliminate bubbles in the slurry.
[0067] The method for preparing the grinding wheel slurry of the present invention comprises the steps of:
[0068] 1. Dry mixing
[0069] mixing abrasive grains, fillers and additives to obtain a powder mixture;
[0070] ㈡Resin prepolymer preparation
[0071] The resin and the diluent are heated and stirred to obtain a resin prepolymer with a viscosity of less than 3000 mPa.s;
[0072] (iii) Preparation of slurry
[0073] The resin prepolymer, the photoinitiator and the thermal initiator are stirred and then added into the powder mixture to obtain a premix, and the premix is ball-milled to obtain a grinding wheel slurry.
[0074] Furthermore, during the preparation process, the abrasive, filler and additive can be sieved through suitable sieves, and after screening, they are poured into a V-type mixer in proportion and mixed for 1 to 2 hours to obtain a powder mixture. The resin and diluent are heated in a heated stirrer, the temperature is raised to a system viscosity of <3000mpa.s, and stirring is started for 5 to 60 minutes to obtain a resin prepolymer. Then, the resin prepolymer, photoinitiator and thermal initiator are added to a mechanical stirrer, stirred for 5 to 60 minutes at a temperature of <55°C, and then the powder mixture is added and stirred for 1 to 2 hours to obtain a premix, and the premix is placed in a wet ball mill and ball milled for 5 to 60 minutes to obtain a slurry.
[0075] The abrasive grains in the grinding wheel slurry of the present invention can be regular particles with edges and corners and have pores on the surface, with a side length of 50 to 2000 μm, a porosity of 10 to 50%, and a pore diameter of 5 to 50 μm. The abrasive grains can be triangular pyramids, quadrangular pyramids, triangular prisms or quadrangular prisms. Compared with spherical abrasive grains, the abrasive grains have edges and corners that can better combine with the cured resin, increase the holding force of the resin on the abrasive grains, and ensure that the abrasive grains can withstand the extrusion when the grinding disc runs at high speed. In terms of weight percentage, the preparation raw materials include 20 to 90 parts of abrasive base material, 20 to 50 parts of quartz powder, 1 to 20 parts of adhesive, 1 to 10 parts of solvent, 1 to 50 parts of high temperature resistant powder and 0 to 10 parts of other additives.
[0076] Among them, the content of the abrasive base material can be but is not limited to 20 parts, 30 parts, 40 parts, 50 parts, 60 parts, 70 parts, 80 parts, and 90 parts. The abrasive base material includes a main abrasive base material and a secondary abrasive base material. The Mohs hardness of the main abrasive base material is at least 8, and it is selected from at least one of diamond, silicon carbide, boron carbide, aluminum oxide, cerium oxide, titanium diboride, tungsten carbide, titanium carbide, cubic boron nitride, garnet, zirconium oxide, and titanium oxide. The hardness and size of the secondary abrasive base material are both smaller than the main abrasive base material, and the Dv50 of the secondary abrasive base material is 0.5 to 9.0 μm and is selected from at least one of diamond, silicon carbide, boron carbide, aluminum oxide, cerium oxide, titanium diboride, tungsten carbide, titanium carbide, cubic boron nitride, garnet, zirconium oxide, and titanium oxide. The secondary abrasive base material is used to assist grinding, improve grinding efficiency, increase the overall fluidity of the system, and facilitate molding processing. If the particle size of the primary abrasive base material is less than 10 μm, that is, the size itself is relatively small, the secondary abrasive base material may not be added.
[0077] The content of quartz powder can be, but is not limited to, 20 parts, 25 parts, 30 parts, 35 parts, 40 parts, 45 parts, and 50 parts. The quartz powder can be a single quartz powder or a mixture of multiple quartz powders with a melting point not higher than 1000° C. The particle size of the quartz powder is smaller than the particle size of the abrasive base. The quartz powder can improve the wear resistance of the abrasive.
[0078] The content of the binder can be, but is not limited to, 1 part, 3 parts, 5 parts, 8 parts, 10 parts, 13 parts, 15 parts, 18 parts, and 20 parts. The binder includes at least one of silicate, phosphate, aluminate, colloidal sodium hydroxide, a saturated aqueous solution of PVA, and dextrin. The volatilization point of the binder is 200-500° C., and it can leave airways and pores while volatilizing during sintering.
[0079] The content of the solvent can be, but is not limited to, 1 part, 2 parts, 3 parts, 4 parts, 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, 10 parts. The solvent includes pure water, further water treated by reverse osmosis, with a conductivity of <10 μs / cm, preferably pure water with a conductivity of <5 μs / cm.
[0080] The content of the high temperature resistant powder can be, but is not limited to, 1 part, 5 parts, 10 parts, 15 parts, 20 parts, 35 parts, 30 parts, 35 parts, 40 parts, 45 parts, and 50 parts. The melting point of the high temperature resistant powder is higher than the sintering temperature of the raw material during sintering. The high temperature resistant powder includes at least one of sodium chloride, sintered alumina, CoCl2, MnCl2, FeCl2, and CaCl2. The high temperature resistant powder can keep the abrasive particles from sticking together during sintering, reduce the deformation of the abrasive particles during sintering, and still maintain good regularity after sintering. It remains stable at the sintering temperature and is easy to be removed after sintering.
[0081] The content of other additives can be, but is not limited to, 0, 1, 2, 3, 4, 5, 6, 7, 8, 9, and 10 parts. Other additives include at least one of a wetting agent, a defoaming agent, and a bactericide. The wetting agent can improve the compatibility between the components, and is preferably an alumina sol wetting agent; the defoaming agent can reduce the bubbles formed during mixing, and is preferably an anionic surfactant; the bactericide can reduce bacterial growth, prolong the storage time of the abrasive particles, and destroy the viscosity of the system, and is preferably an isothiazolinone bactericide.
[0082] The method for preparing abrasive grains in the grinding wheel slurry of the present invention comprises the following steps.
[0083] (I) Mixing
[0084] Mix the formulated amount of abrasive base, quartz powder, binder, solvent and other additives to obtain a thick mixture.
[0085] (ii) Finalization
[0086] The thick mixture is pressed into the cavity of a mold with certain angles and dried to obtain shaped abrasive particles.
[0087] (III) Sintering
[0088] The abrasive grains and high temperature resistant powder are mixed and then sintered, and the melting point of the high temperature resistant powder is higher than the sintering temperature.
[0089] (IV) Post-processing
[0090] The sintered product is cooled and screened to remove the high temperature resistant powder and obtain regular abrasive grains.
[0091] Wherein, the mixing in step (I) can be carried out in a ball mill mixer, and the mixing time is 1 to 2 hours. The depth of the cavity to be shaped in step (ii) is 80 to 2000 μm, the side length of the cavity wall is 80 to 2000 μm, the cavity of the mold is non-spherical / hemispherical, and has certain edges and corners, which are used to make the abrasive particles after forming have certain shapes and edges and corners, and increase the holding force of the resin matrix on the abrasive particles in the later stage. The cavity can be a triangular pyramid, a quadrangular pyramid, a triangular prism or a quadrangular prism, etc. During shaping, a scraper or a leveling rod can be used to completely press the thick mixture into the cavity of the mold, and the excess part of the thick mixture that has not entered the cavity can be scraped off from the top surface of the mold to prevent the excess part from affecting the regularity of the abrasive particles. The mold loaded with the thick mixture is heated to evaporate the water, and can be placed in an oven at a drying temperature of 70 to 130°C. The drying temperature is based on the principle of production economy, but the maximum temperature cannot exceed the thermal deformation temperature of the mold. After drying until the water evaporates to more than 90wt.%, use gravity, shaking, air gun blowing, ultrasonic vibration, vacuum adsorption, or other methods to remove the abrasive particles from the cavity.
[0092] In step (III) sintering, the high temperature resistant powder includes at least one of sodium chloride, sintered alumina, CoCl2, MnCl2, FeCl2 and CaCl2. The maximum sintering temperature is 70-90% of the melting point of the high temperature resistant powder or the maximum sintering temperature is 500-1000°C, and the sintering time is 1-24h. The sintering is carried out in steps, first heating to 300-450°C, then heating to 500-1000°C, and the heating rate of sintering is 1-10°C / min. Maintaining sufficient sintering temperature and sintering time can remove 95wt.% of volatile substances.
[0093] The post-treatment screening in step (IV) is carried out using a water flow particle size classifier, and filtering can be carried out using a filter with a specific pore size while cleaning.
[0094] In order to better illustrate the purpose, technical scheme and beneficial effects of the present invention, the present invention will be further described below in conjunction with specific embodiments. It should be noted that the following implementation method is a further explanation of the present invention and should not be used as a limitation of the present invention.
[0095] Part 1: Regular Abrasive Grains
[0096] Example 1
[0097] This embodiment is a kind of abrasive with regularity. The raw materials for preparation include, by weight percentage, 50 parts of diamond with a Mohs hardness of 10, 10 parts of garnet with a Mohs hardness of 7.2, 35 parts of quartz powder, 10 parts of PVA saturated aqueous solution, 3 parts of water with a conductivity of less than 10μs / cm treated by reverse osmosis, 5 parts of sodium chloride and 2 parts of sodium dodecylbenzene sulfonate.
[0098] The method for preparing the abrasive grains comprises the following steps.
[0099] (I) Mixing
[0100] Diamond, garnet, quartz powder, PVA saturated aqueous solution, water and sodium dodecylbenzene sulfonate were mixed in a ball mill mixer for 2 hours to obtain a thick mixture.
[0101] (ii) Finalization
[0102] The thick mixture is pressed into a triangular prism cavity of a mold, and dried at 100° C. until the water evaporates to more than 90 wt.% to obtain shaped abrasive particles, and then the abrasive particles are separated from the cavity by shaking.
[0103] (III) Sintering
[0104] After mixing the abrasive and sodium chloride, the temperature was first increased to 400°C at a heating rate of 3°C / min, and then increased to 750°C at a heating rate of 5°C / min and sintered for 12h.
[0105] (IV) Post-processing
[0106] After the sintered product is cooled, it is screened by a water flow particle size classifier to remove the high temperature resistant powder and obtain regular triangular prism abrasive grains.
[0107] The obtained triangular prism abrasive grains are as follows Figure 2 As shown, the particles were tested and found to have a side length of 110 to 140 μm, a porosity of 28 to 30%, and a pore diameter of 20 to 24 μm.
[0108] Example 2
[0109] This embodiment is a kind of abrasive with regularity. The raw materials for preparation include, by weight percentage, 85 parts of diamond with a Mohs hardness of 10, 15 parts of cerium oxide with a Mohs hardness of 5.5, 35 parts of a quartz powder mixture, 15 parts of aluminate, 7 parts of water with a conductivity of less than 10μs / cm treated by reverse osmosis, 8 parts of sintered alumina, 1 part of a polyammonium salt wetting agent and 2 parts of a polyether silicone oil defoaming agent.
[0110] The method for preparing the abrasive grains comprises the following steps.
[0111] (I) Mixing
[0112] Diamond, cerium oxide, quartz powder mixture, aluminate, water, polyammonium salt wetting agent and polyether silicone oil defoaming agent are mixed in a ball mill mixer for 2 hours to obtain a thick mixture.
[0113] (ii) Finalization
[0114] The thick mixture is pressed into a quadrangular prism cavity of a mold, and dried at 90° C. until the water evaporates to more than 90 wt.% to obtain shaped abrasive particles, and then the abrasive particles are separated from the cavity by shaking.
[0115] (III) Sintering
[0116] After the abrasive and sintered alumina were mixed, the temperature was first increased to 300°C at a heating rate of 7°C / min, and then increased to 1000°C at a heating rate of 10°C / min and sintered for 10 h.
[0117] (IV) Post-processing
[0118] After the sintered product is cooled, it is screened by a water flow particle size classifier to remove the high temperature resistant powder and obtain regular quadrangular prism abrasive grains.
[0119] The obtained quadrangular prism abrasive grains are as follows Figure 3 As shown, the particles were tested and found to have a side length of 120-140 μm, a porosity of 20-22%, and a pore diameter of 14-16 μm.
[0120] Example 3
[0121] This embodiment is a kind of abrasive grain with regularity. The raw materials for preparation include, by weight percentage, 35 parts of silicon carbide with a Mohs hardness of 9.3, 5 parts of garnet with a Mohs hardness of 7.2, 25 parts of quartz powder, 10 parts of silicate, 3 parts of water with a conductivity of less than 10 μs / cm treated by reverse osmosis, 8 parts of sodium chloride and 3 parts of sodium dodecylbenzene sulfonate.
[0122] The method for preparing the abrasive grains comprises the following steps.
[0123] (I) Mixing
[0124] Silicon carbide, garnet, quartz powder, silicate, water and sodium dodecylbenzene sulfonate were mixed in a ball mill mixer for 1.5 hours to obtain a thick mixture.
[0125] (ii) Finalization
[0126] The thick mixture is pressed into a triangular prism cavity of a mold, and dried at 100° C. until the water evaporates to more than 90 wt.% to obtain shaped abrasive particles, and then the abrasive particles are separated from the cavity by shaking.
[0127] (III) Sintering
[0128] After the abrasive and sodium chloride were mixed, the temperature was first increased to 400°C at a heating rate of 5°C / min, and then increased to 700°C at a heating rate of 10°C / min and sintered for 10 h.
[0129] (IV) Post-processing
[0130] After the sintered product is cooled, it is screened by a water flow particle size classifier to remove the high temperature resistant powder and obtain regular triangular prism abrasive grains.
[0131] The obtained triangular prism abrasive grains were tested and found to have a side length of 450-465 μm, a porosity of 13-15%, and a pore diameter of 15-16 μm.
[0132] Part 2: Grinding wheel slurry
[0133] Example 4
[0134] The present embodiment is a grinding wheel slurry. The raw materials for preparation include, by weight percentage, 15 parts of triangular prism abrasive grains of Example 1, 35 parts of epoxy acrylic resin, 20 parts of n-butyl acrylate, 0.6 parts of 1173 photoinitiator, 0.6 parts of AIBN thermal initiator, 20 parts of flat alumina powder, 10 parts of wollastonite powder, 5 parts of nano-silicon dioxide, 0.25 parts of coupling agent 6040, 0.5 parts of wetting agent W903 and 0.4 parts of defoaming agent BYK-530.
[0135] The preparation method of the grinding wheel slurry comprises the following steps.
[0136] 1. Dry mixing
[0137] The triangular prism abrasive, flat alumina powder, wollastonite powder and nano-silicon dioxide were dried in an oven at 100°C for 5 hours, and then sieved with a 140-mesh sieve. After sieving, they were poured into a V-type mixer according to the formula ratio, and coupling agent 6040 and wetting agent W903 were added and mixed for 2 hours to obtain a powder mixture.
[0138] ㈡Resin prepolymer preparation
[0139] Add epoxy acrylic resin and n-butyl acrylate into a heated stirrer, raise the temperature to 50°C, start stirring, and stir until the resin is completely dissolved to obtain a resin prepolymer.
[0140] (iii) Preparation of slurry
[0141] Add the resin prepolymer, defoamer BYK-530 and powder mixture into a mechanical stirrer and stir for 30 minutes at a temperature below 50°C. Add 1173 photoinitiator and AIBN thermal initiator and continue stirring for 10 minutes.
[0142] The stirred premix was put into a wet ball mill and ball-milled for 30 minutes to obtain a slurry.
[0143] Example 5
[0144] The present embodiment is a grinding wheel slurry. The raw materials for preparation include, by weight percentage, 15 parts of quadrangular prism abrasive grains of Example 2, 45 parts of epoxy acrylic resin, 25 parts of vinyl acetate, 0.6 parts of 1173 photoinitiator, 1.0 parts of benzoyl peroxide, 18 parts of flat alumina powder, 20 parts of nano-silicon dioxide, 0.50 parts of coupling agent 6040 and 0.6 parts of defoaming agent BYK-530.
[0145] The preparation method of the grinding wheel slurry comprises the following steps.
[0146] 1. Dry mixing
[0147] The tetrahedral abrasive particles, flat alumina powder and nano-silicon dioxide were dried in an oven at 100°C for 6 hours, and then sieved with a 140-mesh screen. After sieving, they were poured into a V-type mixer according to the formula ratio, and coupling agent 6040 was added and mixed for 3 hours to obtain a powder mixture.
[0148] ㈡Resin prepolymer preparation
[0149] Add epoxy acrylic resin and vinyl acetate into a heated stirrer, raise the temperature to 50°C, start stirring, and stir until the resin is completely dissolved to obtain a resin prepolymer.
[0150] (iii) Preparation of slurry
[0151] Add the resin prepolymer, defoamer BYK-530 and powder mixture into a mechanical stirrer and stir for 40 minutes at a temperature below 50°C. Add 1173 photoinitiator and benzoyl peroxide and continue stirring for 20 minutes.
[0152] The stirred premix was put into a wet ball mill and ball-milled for 25 minutes to obtain a slurry.
[0153] Example 6
[0154] The present embodiment is a grinding wheel slurry. The raw materials for preparation include, by weight percentage, 30 parts of triangular prism abrasive grains of Example 3, 50 parts of epoxy acrylic resin, 20 parts of n-butyl acrylate, 0.6 parts of 1173 photoinitiator, 0.6 parts of AIBN thermal initiator, 15 parts of flat alumina powder, 20 parts of wollastonite powder, 15 parts of nano-silicon dioxide, 0.25 parts of coupling agent 6040, 0.5 parts of wetting agent W903 and 0.5 parts of defoaming agent BYK-530.
[0155] The preparation method of the grinding wheel slurry comprises the following steps.
[0156] 1. Dry mixing
[0157] After drying the triangular prism abrasive grains, flat alumina powder, wollastonite powder and nano-silicon dioxide in an oven at 100°C for 5 hours, they were sieved with a 140-mesh screen. After sieving, they were poured into a V-type mixer according to the formula ratio, and coupling agent 6040 and wetting agent W903 were added and mixed for 2 hours to obtain a powder mixture.
[0158] ㈡Resin prepolymer preparation
[0159] Add epoxy acrylic resin and n-butyl acrylate into a heated stirrer, raise the temperature to 50°C, start stirring, and stir until the resin is completely dissolved to obtain a resin prepolymer.
[0160] (iii) Preparation of slurry
[0161] Add the resin prepolymer, defoamer BYK-530 and powder mixture into a mechanical stirrer and stir for 40 minutes at a temperature below 50°C. Add 1173 photoinitiator and AIBN thermal initiator and continue stirring for 20 minutes.
[0162] The stirred premix was put into a wet ball mill and ball-milled for 30 minutes to obtain a slurry.
[0163] Comparative Example 1
[0164] This comparative example is a grinding wheel slurry. The raw materials for preparation include, by weight percentage, 15 parts of spherical abrasive particles, 35 parts of epoxy acrylic resin, 20 parts of n-butyl acrylate, 0.6 parts of 1173 photoinitiator, 0.6 parts of AIBN thermal initiator, 20 parts of flat alumina powder, 10 parts of wollastonite powder, 5 parts of nano-silica, 0.25 parts of coupling agent 6040, 0.5 parts of wetting agent W903 and 0.4 parts of defoaming agent BYK-530.
[0165] The preparation method of the grinding wheel slurry comprises the following steps.
[0166] 1. Dry mixing
[0167] Spherical abrasive particles, flat alumina powder, wollastonite powder and nano-silicon dioxide were dried in an oven at 100°C for 5 hours, and then sieved with a 140-mesh screen. After screening, they were poured into a V-type mixer according to the formula ratio, and coupling agent 6040 and wetting agent W903 were added and mixed for 2 hours to obtain a powder mixture.
[0168] ㈡Resin prepolymer preparation
[0169] Add epoxy acrylic resin and n-butyl acrylate into a heated stirrer, raise the temperature to 50°C, start stirring, and stir until the resin is completely dissolved to obtain a resin prepolymer.
[0170] (iii) Preparation of slurry
[0171] Add the resin prepolymer, defoamer BYK-530 and powder mixture into a mechanical stirrer and stir for 30 minutes at a temperature below 50°C. Add 1173 photoinitiator and AIBN thermal initiator and continue stirring for 10 minutes.
[0172] The stirred premix was put into a wet ball mill and ball-milled for 30 minutes to obtain a slurry.
[0173] After vacuum degassing, the slurries prepared in Examples 4 to 6 and Comparative Example 1 were uniformly coated on abrasive tools of corresponding shapes (i.e., the same shape as the abrasive particles) by scraping, and then transferred to a PET substrate with a coating thickness of 1.6 mm. The slurries were cured for 20 seconds under 500 W 365 nm ultraviolet light, and then baked at 80° C. for 4 hours to obtain a composite layer. The composite layer was bonded to a PC board through a 300LSE pressure-sensitive adhesive, and the other side of the PC board was attached with a 300LSE pressure-sensitive adhesive so as to bond with a high-speed grinding disc to obtain a thinning grinding wheel.
[0174] The thinned grinding wheels prepared in Examples 4 to 6 and Comparative Example 1 were subjected to relevant tests, and the results are shown in Table 1.
[0175] The test environment is as follows.
[0176] 1) Equipment: Yuhuan DDG 580 grinder;
[0177] 2) Workpiece: Corning Gorilla 2, 130mm*60mm;
[0178] 3) Cutting fluid flow rate: 30L / min;
[0179] 4) Grinding disc angle: 5°;
[0180] 5) Grinding disc speed: upper disc 700r / min, lower disc 700r / min;
[0181] 6) Processing status: Continuously processing 1000 pieces of glass.
[0182] Glass breakage rate = (number of broken glasses) / (number of processed glasses)
[0183] Deep scratch rate = (the number of glasses with scratches found by QC compared with the internal standard sample) / (the number of processed glasses)
[0184] Grinding wheel wear resistance = thickness of abrasive consumed by 1000 pieces of glass (μm) = ( Figure 1 Height starting from "73")-( Figure 1 "73" is the height after grinding 1000 pieces of glass)
[0185] Table 1 Performance results of thinned grinding wheels of Examples 4 to 6 and Comparative Example 1
[0186] Test items Example 4 Example 5 Example 6 Comparative Example 1 Glass breakage rate / % 2% 2% 3% 30% Deep scratch rate / % 5% 5% 8% 65% Grinding wheel wear resistance 3μm 1μm 2μm 20μm Grinding wheel dressing frequency / times 0 times 1 time 1 time 4 times
[0187] From the results in Table 1, it can be seen that in Examples 1 to 3, due to the regularity of the abrasive particles, the glass breakage rate and deep scratch rate are low, the grinding wheel has high wear resistance and the grinding wheel dressing frequency is low, and the grinding disc angle during the test is 5°, indicating that it has better cutting performance. In addition, compared with the triangular prism, the wear resistance of the grinding wheel is better and the dressing frequency is lower when the quadrangular prism is used. This is because the triangular prism abrasive particles have too sharp edges. Although the thinning speed is fast during processing, the abrasive particles are also subjected to large stress and wear faster, while the quadrangular prism can withstand greater stress, wear slower, and have higher wear resistance.
[0188] Comparative Example 1 uses spherical abrasive particles, which have a certain glass breakage rate and deep scratch rate. The wear resistance of the grinding wheel is poor, and continuous processing of 1,000 pieces of glass requires two grinding wheel dressings, which is difficult to meet the requirements of efficient cutting. When the glass passes through the angle and does not reach the target thickness, the glass will also break.
[0189] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention is described in detail with reference to the preferred embodiments, it is not limited to those listed in the embodiments. Those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A regular abrasive grain, characterized in that: The abrasive material is in the form of regular angular particles with pores on the surface, with a side length of 50 to 2000 μm, a porosity of 10 to 50%, and a pore diameter of 5 to 50 μm. The raw materials for preparation include 20 to 90 parts of abrasive base, 20 to 50 parts of quartz powder, 1 to 20 parts of adhesive, 1 to 10 parts of solvent, 1 to 50 parts of high temperature resistant powder and 0 to 10 parts of other additives, and the melting point of the high temperature resistant powder is higher than the sintering temperature of the raw materials during sintering.
2. The abrasive grains with regularity according to claim 1, characterized in that: The abrasive base includes a main abrasive base and a secondary abrasive base, the hardness and size of the main abrasive base are both greater than those of the secondary abrasive base, and the main abrasive base and the secondary abrasive base are each independently selected from at least one of diamond, silicon carbide, boron carbide, aluminum oxide, cerium oxide, titanium diboride, tungsten carbide, titanium carbide, cubic boron nitride, garnet, zirconium oxide and titanium oxide.
3. The abrasive grains with regularity according to claim 2, characterized in that: The Mohs hardness of the primary abrasive base is at least 8 or the Dv50 of the secondary abrasive base is 0.5-9.0 μm.
4. The abrasive grains with regularity according to claim 1, characterized in that: The invention comprises one of the following features (1) to (9): (1) The quartz powder is a single quartz powder; (2) The quartz powder is a mixture of multiple quartz powders with a melting point not higher than 1000°C; (3) The particle size of the quartz powder is smaller than the particle size of the abrasive base; (4) The binder comprises at least one of silicate, phosphate, aluminate, colloidal sodium hydroxide, saturated aqueous solution of PVA and dextrin; (5) The volatilization point of the adhesive is 200 to 500°C; (6) The solvent includes pure water and has an electrical conductivity of <10 μs / cm; (7) The high temperature resistant powder includes at least one of sodium chloride, sintered alumina, CoCl2, MnCl2, FeCl2 and CaCl2; (8) The other auxiliary agents include at least one of a wetting agent, a defoaming agent and a bactericide; (9) The abrasive grains are triangular pyramids, quadrangular pyramids, triangular prisms or quadrangular prisms.
5. A method for preparing regular abrasive particles, characterized in that: Includes steps: (I) Mixing Mixing the formulated amount of abrasive base, quartz powder, binder, solvent and other additives to obtain a thick mixture; (ii) Finalization The thick mixture is pressed into the cavity of a mold having certain edges and corners, and dried to obtain shaped abrasive particles; (III) Sintering The abrasive grains and high temperature resistant powder are mixed and then sintered, and the melting point of the high temperature resistant powder is higher than the sintering temperature; (IV) Post-processing After the sintered product is cooled, it is screened to remove the high temperature resistant powder and obtain regular abrasive grains.
6. The method for preparing regular abrasive grains according to claim 5, characterized in that: Includes one of the following features ① to ⑩: ① The mixing in step (I) can be carried out in a ball mill mixer, and the mixing time is 1 to 2 hours; ② The depth of the cavity is 80 to 2000 μm, and the side length of the cavity wall is 80 to 2000 μm; ③ The drying temperature is 70-130° C., and the drying is performed until the water evaporates to more than 90 wt.%; ④ The abrasive particles are separated from the cavity by gravity, shaking, air gun blowing, ultrasonic vibration, and vacuum adsorption; ⑤ The high temperature resistant powder includes at least one of sodium chloride, sintered alumina, CoCl2, MnCl2, FeCl2 and CaCl2; ⑥ The maximum sintering temperature is 70-90% of the melting point of the high temperature resistant powder; ⑦ The maximum sintering temperature is 500-1000°C, and the sintering time is 1-24h; ⑧ The sintering is carried out in steps, first heating to 300-450°C, and then heating to 500-1000°C; ⑨ The heating rate of the sintering is 1 to 10°C / min; ⑩ The screening is carried out using a water flow particle size classifier.
7. A grinding wheel slurry, characterized in that: In terms of weight percentage, the raw materials include 7 to 60 parts of abrasive, 30 to 60 parts of resin, 5 to 30 parts of diluent, 0.5 to 5.0 parts of photoinitiator, 0.6 to 4.0 parts of thermal initiator, 40 to 60 parts of filler and 0 to 5 parts of auxiliary agent. The abrasive is the regular abrasive described in any one of claims 1 to 4 or the regular abrasive prepared by the method for preparing regular abrasive described in any one of claims 5 to 6.
8. The grinding wheel slurry according to claim 7, characterized in that: The method comprises one of the following features (i) to (ix): (i) the resin comprises at least one of epoxy resin, acrylic resin and polyurethane; (ii) the surface hardness of the resin after curing is 60 to 95 HA; (iii) the diluent comprises at least one of an acrylate compound, a vinyl compound, a vinyl ether compound and an epoxy compound; (iv) the diluent includes at least one of n-butyl acrylate, isooctyl acrylate, isodecyl acrylate, lauryl acrylate, hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, styrene, vinyl acetate, n-vinyl pyrrolidone, ethylene glycol diacrylate, propylene glycol diacrylate and phenyl glycidyl ether); (v) the photoinitiator comprises at least one of benzoin, benzoin ethyl ether, benzoin butyl ether, benzoin dimethyl ether, 2-hydroxy-2-methyl-1-phenyl ketone, 1-hydroxy-cyclohexyl-phenyl ketone, benzophenone, amine compounds, thioxanthones, camphorquinone, bisimidazole, onium salt, metal organic matter and organosilane compounds; (vi) the thermal initiator is an azo compound or a peroxide compound; (vii) the thermal initiator comprises at least one of azobisisobutyronitrile, azobisisoheptylnitrile, benzoyl peroxide, tert-butyl peroxy-2-ethylhexyl ester, tert-amyl peroxy-2-ethylhexyl ester, 1,1'-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane, tert-amyl peroxyacetate, tert-amyl peroxybenzoate, tert-butyl peroxytrimethylhexanoate, diisopropylbenzene peroxide and di-tert-amyl peroxide; (viii) the filler comprises at least one of kaolin, alumina, nano-silicon dioxide, wollastonite, polyamide wax and talc; (ix) The auxiliary agent includes at least one of a wetting agent, a coupling agent and a defoaming agent.
9. The method for preparing grinding wheel slurry according to claim 7 or 8, characterized in that: Includes steps:
1. Dry mixing Mixing the abrasive grains, the filler and the additive to obtain a powder mixture; ㈡Resin prepolymer preparation The resin and the diluent are heated and stirred to obtain a resin prepolymer with a viscosity of less than 3000 mPa.s; (iii) Preparation of slurry The resin prepolymer, the photoinitiator and the thermal initiator are stirred and then added into the powder mixture to obtain a premix, and the premix is ball-milled to obtain a grinding wheel slurry.
10. A method for preparing a thinning grinding wheel, characterized in that: The method comprises the following steps: coating the grinding wheel slurry described in any one of claims 7 to 8 or the grinding wheel slurry prepared by the method for preparing the grinding wheel slurry described in claim 9 in a mold, transferring the coating to a substrate, and then sequentially performing ultraviolet light curing and thermal curing to obtain a combined layer; adhering the combined layer to one side of a support plate; and adhering a grinding disc to the other side of the support plate.
Citation Information
Patent Citations
Polycrystalline grits and associated methods
CN101001934A
Alkanolamine-modified phenolic resin formulation and coatings for abrasive products
CN101883801A
Formula of abrasive for fine polishing of glass and semiconductor
CN108070357A
Triangular pyramid diamond grinding wheel abrasive grain and preparation method thereof
CN108659791A
Shaped ceramic abrasive particle and method for producing shaped ceramic abrasive particle
CN110891919A